Early Childhood Education Teachers' Creativity in Implementing Deep Learning to Improve Early Childhood Cognitive Abilities at JA Warraihan Kindergarten, Bima City - Nurtanti; Agus Salam; Wahyu Mulyadi (Lembaga Bale Literasi, 2026)
This study aims to analyze the strategies of PAUD teachers in implementing deep learning at JA Warraihan Kindergarten, Bima City. The research used a descriptive qualitative approach with PAUD teachers as subjects. Data was collected through observation, in-depth interviews, and documentation, then analyzed through reduction, presentation, and drawing conclusions. The research focus includes teacher strategies in planning, implementing, and evaluating learning as well as supporting and inhibiting factors. The results show that teachers apply the strategy systematically through three stages. At the planning stage, the teacher adapts activities to the theme and characteristics of the children. In implementation, the teacher acts as a facilitator who encourages exploration and interpretation of learning experiences. In the evaluation, the teacher carries out continuous assessment of the child's development. The use of animal models increases engagement, understanding, and the quality of learning. Supporting factors include teacher creativity and student enthusiasm, while obstacles include limited facilities and teacher understanding.